PROBLEMS AND PROBLEMATIZATIONS. A HISTORY OF THE REGIMES OF TRUTH IN MEDICINE FROM GEORGES CANGUILHEM AND MICHEL FOUCAULT (2023)
The concept of problematization is fundamental into the Foucault's philosophical works. However, the omission of this notion resulted in a stereotype that included their proposals together with those of social constructivism. On the contrary, I suggest that the concept of problematization relates the Foucault's works with Canguilhem's historical epistemology. This has signifi cant effects, to the extent that not only correct the perspective attributed to Foucault under which certain objects are socially constructed, but open a fi eld of research referred to the truth effects in the human being that arise from interactive complex that involves experts, institutions and individuals. In this article I use the example of medical rationality -developed by these authors- for purposes of enlighten his particular way of understanding the history and the philosophy of the medicine from the problems and problematizations. © 2018 Universidad Autonoma Metropolitana, Department of Philosophy. All rights reserved.